2019
DOI: 10.1080/17482631.2019.1693483
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ transition from milk to solid foods - the lived experiences of first-time parents

Abstract: Purpose: During the transition from ingesting milk to ingesting solid food, infants substantiate their eating habits. The present study focuses on this transition. Specifically, it aimed to explore first-time parents’ lived experiences of their infants’ transition from milk to solid foods.Method: The study is based on the descriptive phenomenological approach Reflective Lifeworld Research (RLR). Ten mothers and ten fathers were interviewed twice; when the infants were aged four to five months and again at seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…Overall, parents in this study felt stress regarding making the “right” choices for their infant, especially concerning the introduction of solid foods, and felt responsible for ensuring their child’s needs where met in terms of nutrients and amount of food. A study in Danish parents also found that parents strived to be perfect and responsible when transitioning from a milk-based diet to solid foods and these demands created insecurity and concern [ 24 ]. Similarly, a Swedish study described how parents of infants considered food as highly important to “child health” and perceived feeding issues as something particularly worrying [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, parents in this study felt stress regarding making the “right” choices for their infant, especially concerning the introduction of solid foods, and felt responsible for ensuring their child’s needs where met in terms of nutrients and amount of food. A study in Danish parents also found that parents strived to be perfect and responsible when transitioning from a milk-based diet to solid foods and these demands created insecurity and concern [ 24 ]. Similarly, a Swedish study described how parents of infants considered food as highly important to “child health” and perceived feeding issues as something particularly worrying [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that parents of young children are uncertain or lack knowledge about a healthy diet, daily physical activity, adequate sleep, and limited screen time for their children, and that they experience problems or are unable to facilitate a healthy environment for their child [ 21 25 ]. Moreover, the transition to parenthood is a major adjustment period and is known to be a time where the need for support is increased, since it comes with profound life changes and considerable stress [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in sweets in this age group is something common, and total prohibition can cause the preschooler to crave it even more. Ideally, the family should explain in easy terms the benefits and harms of each type of food, in addition to having healthy habits to allow preschoolers to learn by imitation (Arikpo et al, 2018;Bell et al, 2018;Norlyk, Larsen, & Kronborg, 2019;Sociedade Brasileira de Pediatria, 2012;Tully et al, 2019). In this work, many preschoolers ate outside mealtimes, always extremely sugary foods, and drinking soda and artificially sweetened juice during meals was also widely reported by parents.…”
Section: Discussionmentioning
confidence: 92%
“…The food is directly related to general and oral health. It is important for families to incorporate healthy habits in their daily lives and perpetuate them from one generation to the next (Arikpo et al, 2018;Bell et al, 2018;Brazil, 2019;Sociedade Brasileira de Pediatria, 2012;Norlyk, Larsen, & Kronborg, 2019;Tully et al, 2019). Ensuring a healthy lifestyle, in addition to being a child's right, is the responsibility of their parents/guardians, health professionals and educators (Chomitz et al, 2019;Nishide et al, 2018;Paglia, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation